Reflections on the Multilateral Instrument and its connection with the Peruvian legal system: the case of the permanent establishment - García Santos, Frank Fermín (2019)
The fight against base erosion and profit shifting has been pointed out by the OECD as a problem that requires a coordinated response among the various jurisdictions around the world. As a proposed solution, the OECD has promoted the Multilateral Convention, as the instrument that collects the BEPS Action Plan reports. However, its incorporation requires profound reflections on the relationship between this instrument and our treaties and its impact on domestic legislation, due to the complexity that comes with the addition of a third law layer. The concept of permanent establishment of the Multilateral Instrument is one of the issues that requires such analysis. Providing interpretative content to this concept can be determinant to establishing the power to impose of various jurisdictions that are part of the Multilateral Instrument, which will translate into the success or failure of OECD efforts.